SELF IMAGE MAHASISWA DALAM GAYA HIDUP METROSEKSUAL (STUDI PADA MAHASISWA UNIVERSITAS RIAU) - Rizal Dhiky Hermawan; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
A negative self-image can lead to low self-confidence, whereas a positive self-image can lead to a positive response. This trend has led to a shift in the perception of the term, with university students showing a higher interest in appearance, self-care, and modern lifestyles. Riau University, a leading university in Riau Province, is a prime example of this trend, with its students focusing on appearance and fitness as well as a positive self-image. This study aims to determine the activities, motivations, and self-image formation of students through body care and fitness activities using the approaches of Symbolic Interactionism Theory by George Herbert Mead, Hyperreality by Jean Baudrillard, and Lifestyle Theory by Kotler and Keller. The subjects selected in this study were six informants and one triangulator using the purposive sampling technique. This type of research is field research and uses a qualitative approach by Miles and Huberman. Data collection techniques using observation, interviews, and documentation The results of this study indicate that the media plays an important role in motivating individuals to achieve goals and influencing self-image and self-perception. The media industry, including social and intellectual media, influences self-perception through various factors, such as social status, family, and personal experience. The media aims to create products and services that promote self-perception, helping individuals achieve an idealized self-image. Keywords: Self-Image, Metrosexual, Media.